Multifunctional Properties of Chicken Embryonic Prenatal Mesenchymal Stem Cells- Pluripotency, Plasticity, and Tumor Suppression - Bhuvanalakshmi, G.; Arfuso, Frank; Dharmarajan, Arunasalam; Warrier, Sudha (Springer US, 2014)
The chick embryo represents an accessible and economical in vivo model, which has long been used in developmental biology, gene expression analysis, and loss/gain of function experiments. In the present study, we assessed and characterized bone marrow derived mesenchymal stem cells from prenatal day 13 chicken embryos (chBMMSCs) and determined some novel properties. After assessing the mesenchymal stem cell (MSC) properties of these cells by the presence of their signature markers (CD 44, CD 73, CD 90, CD 105, and vimentin), we ascertained a very broad spectrum of multipotentiality as these MSCs not only differentiated into the classic tri-lineages of MSCs but also into ectodermal, endodermal, and mesodermal lineages such as neuron, hepatocyte, islet cell, and cardiac. In addition to wide plasticity, we detected the presence of several pluripotent markers such as Oct4, Sox2, and Nanog. This is the first study characterizing prenatal chBMMSCs and their ability to not only differentiate into mesenchymal lineages but also into all the germ cell layer lineages. Furthermore, our studies indicate that prenatal chBMMSCs derived from the chick provide an excellent model for multi-lineage development studies because of their broad plasticity and faithful reproduction of MSC traits as seen in the human. Here, we also present evidence for the first time that media derived from prenatal chBMMSC cultures have an anti-tumorigenic, anti-migratory, and pro-apoptotic effect on human tumors cells acting through the Wnt-ß-catenin pathway. These data confirm that chBMMSCs are enriched with factors in their secretome that are able to destroy tumor cells. This suggests a commonality of properties of MSCs across species between human and chicken.